2011
DOI: 10.1016/j.biopsych.2010.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Chlorzoxazone, an SK-Type Potassium Channel Activator Used in Humans, Reduces Excessive Alcohol Intake in Rats

Abstract: Background-Alcoholism imposes a tremendous social and economic burden. There are relatively few pharmacological treatments for alcoholism, with only moderate efficacy, and there is considerable interest in identifying additional therapeutic options. Alcohol exposure alters SKtype potassium channel (SK) function in limbic brain regions. Thus, positive SK modulators such as chlorzoxazone (CZX), an FDA-approved centrally-acting myorelaxant, might enhance SK function and decrease neuronal activity, resulting in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
66
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 59 publications
8
66
0
1
Order By: Relevance
“…Thus, although tightly regulated exogenously applied calcium seems to affect brain function and disease. Therefore, we speculate that acamprosate treatment may enhance brain calcium levels and thereby the activity of calcium-dependent ion channels including the SK2 channels, which may reduce hyperglutamatergic activity and alcohol consumption (Mulholland et al, 2011;Hopf et al, 2011). Second, in alcohol-dependent patients, impairment in electrolyte regulation is often observed and a calcium bolus might counteract this impairment leading to well being and less alcohol consumption.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, although tightly regulated exogenously applied calcium seems to affect brain function and disease. Therefore, we speculate that acamprosate treatment may enhance brain calcium levels and thereby the activity of calcium-dependent ion channels including the SK2 channels, which may reduce hyperglutamatergic activity and alcohol consumption (Mulholland et al, 2011;Hopf et al, 2011). Second, in alcohol-dependent patients, impairment in electrolyte regulation is often observed and a calcium bolus might counteract this impairment leading to well being and less alcohol consumption.…”
Section: Discussionmentioning
confidence: 96%
“…Calcium and acamprosate R Spanagel et al hyperglutamatergic activity and alcohol consumption in rats (Mulholland et al, 2011;Hopf et al, 2011), finally and most importantly, (iv) clinical studies from the early 1950s proposed calcium therapy (at that time called calmonose) for the treatment of alcoholism (O 'Brien, 1952;O'Brien 1964). Our data suggest that acamprosate may also act as a calcium therapy and indeed the application of a daily recommended dose of 1998 mg of Campral leads to enhanced calcium plasma levels in alcohol-dependent patients.…”
Section: Discussionmentioning
confidence: 99%
“…2 bottom). This means that the determined EC 50 values for Ca 2C , calculated from Ca 2C -concentration response curves, decreases as the concentration of modulator increases. Using fast application of different intracellular Ca 2C concentrations to insideout patches, it has furthermore been shown that 1-EBIO has no effect on activation time constant, whereas it strongly reduces the deactivation constant.…”
Section: Pharmacological Modulation Of Ion Channel Gatingmentioning
confidence: 99%
“…37 Despite having a very "rich" ion channel pharmacology, including block of voltagedependent Na C (Na v ) channels (but not glutamate receptors even though its therapeutic action is often referred to as being anti-glutamatergic), the activation of KCNN channels is among riluzole's most potent effects. 38 Two molecules also belonging to the benzimidazole/benzothiazole prototype K Ca activator class are NS309, a very potent molecule (EC 50 10-20 nM for K Ca 3.1 and »600 nM for K Ca 2 channels) and very useful for in vitro mechanistic work, and SKA-31, which was optimized from riluzole with the aim of getting better selectivity (inactive on Na v channels) and maintaining good in vivo properties. 38,39 The very close analogs, SKA-111 and SKA-121, exhibit much higher K Ca 3.1/K Ca 2 selectivity, and accentuate the primary role of the benzimidazole/benzothiazole series as being K Ca 3.1 activators.…”
Section: Pharmacological Modulation Of Ion Channel Gatingmentioning
confidence: 99%
See 1 more Smart Citation